(untitled) (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2024)
Sonar image object detection is an important part of underwater exploration, submarine rescue, hostile object reconnaissance, and other critical maritime tasks. Accurate and efficient detection of objects in sonar imagery plays a key role in ensuring operational success in these domains. The breakthrough of deep learning-related technologies has brought new opportunities for the development of sonar image object detection. By leveraging advanced machine learning techniques, researchers have developed systems capable of achieving higher accuracy and robustness compared to traditional detection methods. However, despite these advancements, the relevant systematic research and practical applications remain insufficiently explored. Traditional approaches often struggle with challenges such as noise, low resolution, and the dynamic underwater environment, which limit their effectiveness. In contrast, deep learning models, with their data-driven advantages, have demonstrated significant potential in overcoming these challenges by learning robust feature representations from large-scale datasets. To address these gaps, a sonar image object detection system is designed to meet the requirements of accuracy, speed, portability, extensibility, and deployment adaptability in real-world scenarios. The system architecture is modular, consisting of three interdependent subsystems: dataset generation, algorithm model training and testing, and model deployment. The dataset generation subsystem ensures high-quality annotated sonar data, which is critical for effective model training. The training and testing subsystem incorporates state-of-the-art deep learning algorithms to optimize detection performance. Finally, the deployment subsystem focuses on translating the trained models into practical applications, ensuring they meet operational requirements under diverse environmental conditions. The system has been applied to underwater suspicious object detection tasks, addressing a range of scenarios requiring precise identification and localization of targets. The experimental results demonstrate that the object detection system achieves reliable and accurate performance, providing good test data and exhibiting excellent application outcomes. This work contributes to advancing the field of sonar image object detection, paving the way for future innovations in underwater exploration and related disciplines.